Patriotisme philanthropique et citoyenneté féminine : les femmes et la Primrose League, 1914-1918 - Philippe Vervaecke (Revue LISA)
This article studies women’s participation in the work of philanthropic patriotism conducted by the Primrose League, a Conservative organisation which remained in activity throughout the First World War. The case of the Primrose League, whose female membership carried out the sort of philanthropic work that conformed to the traditional view of the sexual division of labour, is used to qualify the historiographical interpretation according to which during the war women’s social status went through a dramatic evolution. Discussion then turns to the ambiguous relation of the League’s hierarchy towards the issue of women’s citizenship, which highlights the fact that this organisation embodied a desire to resist the gender disturbances occasioned by the war.